2019
DOI: 10.3390/ijerph16132278
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Sleep Patterns, Health Risk Behaviors, and Health Outcomes among School-Based Population of Adolescents: A Panel Analysis of the Korean Children and Youth Panel Survey

Abstract: Sleep patterns among adolescents are related to health outcomes and health risk behaviors. This study aimed to describe sleep patterns of Korean adolescents and to find the association between sleep patterns and health risk behaviors and health outcomes. Using the junior high school students’ panel data (n = 2351, 12–15 years old) from the Korean Children and Youth Panel Survey, this study described the sleep patterns operationalized as rising time, bedtime, and sleep duration both on weekdays and weekends. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
12
0
5
Order By: Relevance
“…The digital infrastructure is highly developed, which has enabled Koreans to have a high ranking in internet usage worldwide [20], which in turn has led to extended screen time and reduced sleeping hours in Korea. Several studies reported that these factors are associated with health outcomes [21,22,23,24]. Therefore, meal timing and frequency may be important determinants of metabolic disease in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The digital infrastructure is highly developed, which has enabled Koreans to have a high ranking in internet usage worldwide [20], which in turn has led to extended screen time and reduced sleeping hours in Korea. Several studies reported that these factors are associated with health outcomes [21,22,23,24]. Therefore, meal timing and frequency may be important determinants of metabolic disease in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The sex difference in adolescents is also demonstrated in this study. The difference may be due to male adolescents being more affected by the family environment than female adolescents [30].…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the findings of the longitudinal study by Kim et al among adolescents to evaluate the associations of sleep patterns, health outcomes, and health risk behaviors. 42 It was indicated that shorter sleep duration was related to obesity. 42 These results are corroborated by the reports indicating that shorter sleep time has contributed to the obesity epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…42 It was indicated that shorter sleep duration was related to obesity. 42 These results are corroborated by the reports indicating that shorter sleep time has contributed to the obesity epidemic. [43][44][45][46][47] Wheaton et al indicated that short sleep duration was associated with unhealthy weight-control behaviors that can result to being obese.…”
Section: Discussionmentioning
confidence: 99%